How Important is Social Cohesion to Heritage Landscape Preservation and Interpretation? - Themudo Barata, Filipe (2014)
The preservation and interpretation of landscape heritage depends not only on natural and cultural elements, but also on the existence of traditional practices, technical knowledge, ways of understanding nature and social cohesion. Efforts towards landscape maintenance often forget to refer to social cohesion factors. Our scope is to debate ideas comparing two landscapes, which present different social cohesion strengths: the Soajo terraces, in northeast Portugal and Alentejo ‘montado’, in southern Portugal. The social evolution and ecological dynamics vary significantly in the two. To safeguard heritage, the cultural landscape should be duly interpreted. This means, particularly for educational purposes, that the ecological, social and even economic factors which have conditioned the landscape structures should be fully analyzed and understood.